Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Why is it that for any non-negative matrix $M$ and unitary matrix $U$, we have


This question has to do with Problem 2c from this sheet. I think I am allowed to assume the "fact" but I'd like to know why.

share|cite|improve this question

migrated from Nov 9 '13 at 22:30

This question came from our site for active researchers, academics and students of physics.

up vote 7 down vote accepted

Suppose $\sqrt{ U M U^\dagger } = B$. Then $$ B^2 = U M U^\dagger \implies U^\dagger B^2 U = M \implies \left( U^\dagger B U \right) \left( U^\dagger B U \right) = M $$ This implies $$ \left( U^\dagger B U \right)^2 = M $$ Now since $M$ is a positive definite operator, we can take a square root of both sides. We then find $$ U^\dagger B U = \sqrt{M} \implies B = U \sqrt{M} U^\dagger $$ Thus $$ \boxed{ \sqrt{U M U^\dagger} = U \sqrt{M} U^\dagger } $$

share|cite|improve this answer

Hint: Use that to prove that two non-negative operators $P,Q\geq 0$ are equal $P=Q$, it is enough to prove that $P^2=Q^2$.

share|cite|improve this answer

Lets take $M = P D P^{-1}$, where $D$ is diagonal, (assuming $M > 0$), then

$\sqrt{M} = P D^{\frac{1}{2}} P^{-1}$


$\sqrt{U M U^\dagger } = (P U) D^{\frac{1}{2}} (P U)^{-1}$ where now $PU$ diagonalizes $M$ (and the eigenvalues are unchanged, so the diagonal matrix is still $D$.

$D = P^{-1} M P = P^{-1} (U^{-1} U) M (U^{-1} U) P = (UP)^{-1} M (UP)$

Hmm, I have my Us and Ps mixed up. Will fix when I have a chance.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.